Analisis Semiotika Pesan Moral dalam Anime Demon Slayer: Mugen Train - Winduwati, Septia; Wahyutristama, Biyan Nugraha (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
The research examines the moral messages contained in the film Demon Slayer: Mugen Train. The issue in this research how is the moral message contained in the film. In conducting this research the author uses qualitative research methods by using data collection techniques in the form of interviews and documentation. In conducting the research the author also applies mass communication theory which focuses on films as mass communication products and the theory of moral concepts in Japanese culture to find out what kind of moral values ​​are formed in Japan. The results of the research using Ronald Barthes' semiotic analysis get a denotative meaning, namely the struggle of Tanjirou and his friends and Rengoku in eradicating demons. The connotative meaning in this research is the tenacity and courage and unyielding attitude of the character of Tanjirou and his friends. From the analysis based on the moral concept of Japanese culture, moral messages are included in the categories of self-development, relationships with other people, and relationships with the community or society. In the concept of Bushido's moral teachings, there are moral messages that reflect the teachings of Confucianism. Penelitian ini membahas tentang pesan-pesan moral yang terkandung dalam film Demon Slayer: Mugen Train. Permasalahan dalam penelitian ini adalah bagaimana pesan moral yang terkandung dalam film tersebut. Dalam melakukan penelitian, penulis menggunakan metode penelitian kualitatif dengan menggunakan teknik pengumpulan data berupa wawancara dan studi dokumentasi. Penulis juga menerapkan teori komunikasi massa yang berfokus pada film sebagai produk komunikasi massa. Teori konsep moral dalam budaya Jepang untuk mencari tahu seperti apa nilai moral yang terbentuk dalam negara Jepang. Hasil dari penelitian dengan menggunakan analisis semiotik Ronald Barthes mendapatkan makna denotatif yaitu perjuangan Tanjirou dan kawan-kawan serta Rengoku dalam membasmi iblis. Makna konotatif yakni kegigihan serta sikap pemberani dan pantang menyerah dari karakter Tanjirou dan kawan-kawan. Dari analisis berdasarkan konsep moral budaya Jepang mendapatkan pesan-pesan moral yang termasuk dalam kategori pengembangan diri, hubungan dengan orang lain, dan hubungan dengan komunitas atau masyarakat. Dalam konsep ajaran moral Bushido didapatkan pesan moral yang mencerminkan ajaran Konfusianisme.